Proceedings of the 33rd ACM Conference on Hypertext and Social Media 2022
DOI: 10.1145/3511095.3531283
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Vaccination Movements on YouTube in the United States and Brazil

Abstract: In the context of COVID-19 pandemic, social networks such as Facebook, Twitter, YouTube and Instagram stand out as important sources of information. Among those, YouTube, as the largest and most engaging online media consumption platform, has a large influence in the spread of information and misinformation, which makes it important to study how the platform deals with the problems that arise from disinformation, as well as how its users interact with different types of content. Considering that United States … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…By one calculation, social media accounts held by so-called anti-vaxxers increased their following by at least 7.8 million from 2019 to 2020, 1 million people follow anti-vaccine groups on Facebook, and 17 million people subscribe to similar accounts on YouTube (Burki, 2020). Social media companies such as YouTube took actions to remove anti-vaccine content, though some work found that only a small portion of anti-vaccine videos were being removed (Locatelli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By one calculation, social media accounts held by so-called anti-vaxxers increased their following by at least 7.8 million from 2019 to 2020, 1 million people follow anti-vaccine groups on Facebook, and 17 million people subscribe to similar accounts on YouTube (Burki, 2020). Social media companies such as YouTube took actions to remove anti-vaccine content, though some work found that only a small portion of anti-vaccine videos were being removed (Locatelli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate the scientific contribution made by our study. They also highlight that YouTube remains a key hosting provider for alternative and extremist channels, helping them continue to profit from their audience (28,29) and reinforcing concerns about lax content moderation on the platform (30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comments on online content are known to shape viewers' perceptions of the content itself [16,17]. However, the comment section is often plagued by uncivil comments [18][19][20], particularly on anti-vaccine videos [21]. Empirical and quantitative evidence of the influence of toxic comments on other users would provide valuable insights for social media platforms to effectively moderate content and maintain a safe and informative environment.…”
mentioning
confidence: 99%